An ANALISIS FAKTOR STRES AKADEMIK PADA MAHASISWA PRODI PENDIDIKAN ADMINISTRASI PERKANTORAN UNESA MENGGUNAKAN METODE EDUCATIONAL STRESS SCALE FOR ADOLESCENTS: ANALYSIS OF ACADEMIC STRESS FACTORS IN OFFICE ADMINISTRATION EDUCATION STUDY PROGRAM STUDENTS AT UNESA USING THE EDUCATIONAL STRESS SCALE FOR ADOLESCENTS METHOD - Kurniawan, Duddin Dwi (LPPM Press, 2025)
This research is based on the phenomenon of stress and depression throughout the world. This quantitative research aims to analyze the factors of academic stress formed using the Educational Stress scale for Adolescents method. This research was conducted using Multivariate analysis techniques using Confirmatory Factor Analysis statistical analysis. The data collection technique was carried out by distributing questionnaires to Office Administration Education students of the 2021-2024 class of UNESA. The software used to process the data for this study was IBM SPSS STATISTICS 22. The results of this study indicate that there are three (3) factors that form academic stress, namely; 1) Despondency with a percentage of Eigenvalues ​​​​variance formed of 47.36%, this factor describes hopelessness, helplessness and loss of enthusiasm due to academic pressure and high self-expectations. 2) Workload with a percentage of Eigenvalues ​​​​variance formed of 8.06%, this indicates that the number of assignments and homework piling up as well as complicated tests/exams. 3) Worry about grades with a percentage of Eigenvalues ​​Variants formed of 7.77%, this shows that students' worries about grades or academic achievement are a specific source of stress.